Aesthetic On The “Kaulinan” Of Sundanese, Kolecer - Sonson Nurusholih; Gandara Permana (Balong International Journal of Design, 2018)
In Indonesia, there are varieties of games with different cultural backgrounds, having value  and meaning contained in the game or toy. Many meanings are contained in every traditional game bounded by culture not universally. Every meaning has an aesthetic value relating to the attitudes and habits of the people where the toys are located. Likewise with the traditional game of Sundanese Kolecer, which will be made as object of the research. In this research, the author will study the aesthetics contained in Kaulinan Sunda Kolecer. The purpose of this research is to know the meaning of Kaulinan Sunda Kolecer. The study was conducted by using descriptive method with a paradoxical aesthetic approach. The results of the study found that kolecer as an artefact and kokoleceran as toy (kaulinan) of Sundanese people which have philosophical and educational values.Keywords—. Traditional Games, Kaulinan Sunda, Kolecer